2005
DOI: 10.1111/j.1365-2230.2005.01813.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profiles of vitiligo in China: an analysis of 3742 patients

Abstract: Very few articles have aimed to illuminate the clinical profiles of vitiligo in China. We conducted this retrospective survey involving 4118 outpatients with vitiligo in order to identify the differences among various clinical types of vitiligo and their associated disorders. Completed questionnaires (3742) were validated and analysed. Of this large cohort, 1565 (41.8%) individuals presented vitiligo vulgaris, followed by focal, segmental, acrofacial, and universal, in that order. The mean age of vitiligo onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
79
6
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 19 publications
18
79
6
2
Order By: Relevance
“…Em dois trabalhos realizados com pacientes de diferentes idades, o vitiligo focal foi a manifestação inicial na maioria dos casos, coincidindo com os dados encontrados neste trabalho. 13,14 Em relação à superfície corporal afetada, o acometimento era mínimo (inferior a 1%) em 71,8% dos casos, sendo que nenhum paciente apresentava acometimento superior a 50%. Estudo que faz referência à superfície corporal acometida também encontrou pequeno percentual, com 96,4% dos pacientes mostrando acometimento inferior a 20%.…”
Section: Discussionunclassified
“…Em dois trabalhos realizados com pacientes de diferentes idades, o vitiligo focal foi a manifestação inicial na maioria dos casos, coincidindo com os dados encontrados neste trabalho. 13,14 Em relação à superfície corporal afetada, o acometimento era mínimo (inferior a 1%) em 71,8% dos casos, sendo que nenhum paciente apresentava acometimento superior a 50%. Estudo que faz referência à superfície corporal acometida também encontrou pequeno percentual, com 96,4% dos pacientes mostrando acometimento inferior a 20%.…”
Section: Discussionunclassified
“…Increased frequency of type 1 diabetes mellitus and scleroderma was not found. 3,4,7,21 The presence of autoimmune hepatitis or parotiditis was not cited in the literature. The increased frequency of autoimmune diseases in patients with vitiligo suggests that all these conditions share a common etiologic factor.…”
Section: Discussionmentioning
confidence: 99%
“…5 Adults and children of both genders are equally affected, but some studies indicate a slight prevalence of cases among females, possibly due to greater psychosocial consequences caused by this skin condition; however, this 2.6 is not considered statistically significant because some studies show similar rates for both genders. 7 The site of onset and distribution of lesions differ according to age and region of the study population, but the most affected sites are, respectively, the head, limbs and trunk; the less affected sites are mucous membranes. 8,9 This pigmentation disorder follows a suggested classification because not all cases behave in the same way.…”
Section: Introductionmentioning
confidence: 99%
“…Age of onset of disease was 20.9 ± 13.7. Most of studies demonstrated the onset of vitiligo was generally at less than 30 years in age [21,22]. Vitiligo does not show any significant association with gender (P=0.10).…”
Section: Discussionmentioning
confidence: 99%